Meningkatkan Kemampuan Berpikir Kritis Peserta Didik Pada Pembelajaran IPS di Sekolah Dasar Menggunakan Model PBL - Hafni Fauziyyah; Fannia Sulistiani Putri; Tin Rustini (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this study was to determine the appropriate learning model in social science learning in elementary schools. There are still many teachers who use conventional learning models when learning social studies in elementary schools, but currently the learning models have varied, one of which is the Problem-Based Learning model. In this PBL model, students are faced with a problem in solving this problem, students are required to think at a higher level. In this study, the researcher used a qualitative descriptive method while the data collection technique used a literature study. The results of this study indicate that there are differences in student learning outcomes using problem-based learning models with conventional learning models.